Black African Refugee Students in an Era of American Isolationism - Johnson, Ane; Hailu, Meseret (International Higher Education, 2025)
<h3 id="this-article-examines-the-racialized-transformation-of-united-states-refugee-policy-and-its-consequences-for-higher-education-with-attention-to-black-african-refugee-students-it-argues-that-exclusionary-federal-actions-marginalize-displaced-populations-and-erode-longstanding-humanitarian-commitments-although-universities-continue-to-serve-as-contested-but-critical-sites-of-resistance-these-policies-have-compromised-the-countrys-moral-authority-intensifying-us-ethnopolitical-isolationism-is-undermining-the-nations-global-reputation-as-a-leader-in-higher-education" data-pm-slice="1 1 []">This article examines the racialized transformation of United States refugee policy and its consequences for higher education, with attention to Black African refugee students. It argues that exclusionary federal actions marginalize displaced populations and erode longstanding humanitarian commitments. Although universities continue to serve as contested but critical sites of resistance, these policies have compromised the country’s moral authority. Intensifying US ethnopolitical isolationism is undermining the nation’s global reputation as a leader in higher education.